Replication Data for: Spatial Variation in Tree Density and Estimated Aboveground Carbon Stocks in Southern Africa - Tamene, Lulseged D.; Mponela, Powell; Sileshi, Gudeta W.; Chen, Jiehua; Tondoh, Jérôme E. (International Center for Tropical Agriculture, 2017)
Replications dataset for paper that uses large dataset to analyses the spatial variability of above ground biomass carbon.